Evaluating ski base structures - Guo, S.; Love, G.; Brown, C. A. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: Ski base structure, i.e., the topography of ski bases, influences their sliding properties. This paper proposes comparison methods for instruments that measure ski base structure using multiscale analyses and characterizations. One is a traditional laboratory instrument, the other can be used in the field. Brown (2021) describes four principles, two axioms on scales and characterizations and two corollaries on measurement and statistics. Value in surface metrology can come from ability to discriminate topographies that are processed or that perform differently. Ski base topographies, similar to most, have important irregular components that defy apt characterization or modeling with conventional methods.